2022
DOI: 10.1002/biot.202200271
|View full text |Cite
|
Sign up to set email alerts
|

Rsn‐2‐mediated directed foam enrichment of β‐lactamase

Abstract: Today, the availability of methods for the activity-preserving and cost-efficient downstream processing of enzymes forms a major bottleneck to the use of these valuable tools in technical processes. A promising technology appears to be foam fractionation, which utilizes the adsorption of proteins at a gas-liquid interface. However, the employment of surfactants and the dependency of the applicability on individual properties of the target molecules are considerable drawbacks. Here, we demonstrate that a revers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This indicated that GLEGB cell lysis solution had better foaming property and foam stability than Glu. As can be seen from Figure c, the surface tension of GLEGB decreased faster, and the equilibrium surface tension was lower than that of Glu, indicating that the adsorption capacity of GLEGB at the gas–liquid interface was stronger than that of Glu …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This indicated that GLEGB cell lysis solution had better foaming property and foam stability than Glu. As can be seen from Figure c, the surface tension of GLEGB decreased faster, and the equilibrium surface tension was lower than that of Glu, indicating that the adsorption capacity of GLEGB at the gas–liquid interface was stronger than that of Glu …”
Section: Resultsmentioning
confidence: 92%
“…As can be seen from Figure 3c, the surface tension of GLEGB decreased faster, and the equilibrium surface tension was lower than that of Glu, indicating that the adsorption capacity of GLEGB at the gas− liquid interface was stronger than that of Glu. 33 3.1. Foam Property.…”
Section: Resultsmentioning
confidence: 99%
“…However, various parameters governing process efficiency need to be optimized and controlled for efficient purification including pH, temperature, water hardness, surface tension, surfactant concentration, etc. [91].…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…Gas–liquid contacting apparatuses such as bubble columns are potentially useful for treating CO 2 -containing gas with biochemical approaches. One of the critical problems associated with the gas–liquid system is the bubbles-induced decrease in the enzyme activity as reported, for example, with respect to lysozyme , and β-lactamase . Effects of gas bubbles on the stability and conformation of enzymes were examined , partly with the purpose of optimizing foam fractionation bioprocesses for effective or selective recovering of proteins of interest.…”
Section: Introductionmentioning
confidence: 99%
“…One of the critical problems associated with the gas−liquid system is the bubbles-induced decrease in the enzyme activity as reported, for example, with respect to lysozyme 18,19 and β-lactamase. 20 Effects of gas bubbles on the stability and conformation of enzymes were examined 21,22 partly with the purpose of optimizing foam fractionation bioprocesses for effective or selective recovering of proteins of interest. The pH-dependent adsorption of lysozyme to the gas−liquid interface was correlated with the secondary structure of the enzyme.…”
Section: Introductionmentioning
confidence: 99%